Upper airway, obstructive sleep apnea, and anesthesia - Hillman, D.; Eastwood, Peter (2013)
The tendencies to upper airway obstruction during sleep and anesthesia are related. Loss of consciousness in either state increases upper airway collapsibility and anesthesia-related suppression of rousability confers great vulnerability to its effects. This vulnerability increases perioperative risk of obstruction in patients with predisposed airways, such as those with obstructive sleep apnea. This risk diminishes with emergence from anesthesia and return of arousal responses but is likely to recur with postoperative sedation/narcotics. It can be adversely influenced by individual drug sensitivities, posture, postsurgical upper airway edema/hematoma, or hypoventilation/hypercapnia. Close postoperative observation is required until consistent rousability returns.